Activation mechanism of fatty acids on membrane-bound polyphenol oxidase in peach fruit: Conformational change analysis and molecular docking simulation - Zhu, Qiufang; Jiang, Shu; Wei, Yingying; Chen, Yi; Ye, Jianfen; Ding, Phebe; Shao, Xingfeng (Elsevier, 2024)
Polyphenol oxidase (PPO) is the main enzyme initiating internal browning in peach fruit stored at low temperature. Previous studies showed fatty acids activated PPO, but its specific effect and mechanism of activation on PPO are still not clear. Thus, the effects of fatty acids on the biochemical properties and structural conformation of PPO were studied, with sodium dodecyl sulfate used as comparison. The highest degree of activation (5 folds) of membrane-bound PPO (mPPO) was found with 2.2 mM linoleic acid (LA) and its optimal activity was observed also around pH 7.0. Further structure analysis showed LA led to an increase of α-helix content of mPPO from 23.53% to 52.33%; the maximum emission wavelength of treated mPPO shifted from 338 to 340 nm with the fluorescence intensity increased from 446 to 510. LA also can form hydrogen bonds and hydrophobic interactions with mPPO. These results indicated that LA could contribute to a more stable and open enzyme structure, thus activated mPPO. The results will provide more information for PPO activation that highly probably occurs in postharvest peach fruit and its relationship with internal browning. © 2024 Elsevier Ltd